The cloning of Ty1-copia-like retrotransposons from 10 varieties of banana (Musa sp.) - Teo, C.H.; Tan, S.H.; Othman, Y.R.; Schwarzacher, T. (Taylor and Francis Group, 2002)
Ty1-copia-like retrotransposons have been identified and investigated in several plant species. Here, the internal region of the reverse transcriptase (RT) gene of Ty1-copia-like retrotransposons was amplified by PCR from total genomic DNA of 10 varieties of banana. Two to four clones from each variety were sequenced. Extreme heterogeneity in the sequences of Ty1-copia-like retrotransposons from all the varieties was revealed following sequence analysis of the reverse transcriptase (RT) fragments. The size of the individual RT gene fragments varied between 213 and 309 bp. Southern blots of genomic DNA digested from Musa acuminata and other banana varieties probed with W8 clone from M. acuminata and A4 clone from Pisang Abu Nipah showed similar strong, multiple restriction fragments together with other faint hybridization band patterns with variable intensities indicating the presence of many copies of the Ty1-copia-like retrotransposons in the genomes. There was no correlation between retroelement sequence and the banana species (with A or B genomes) from which it arose, suggesting that the probes are not useful for tracking genomes through breeding populations.